Projeto, construção e caracterização de um amortecedor ativo controlado por atuador piezoelétrico - Teixeira, Rafael Luís (2007)
This thesis presents the design methodology, the construction of a prototype and the experimental validation of an active vibration damper witch is controlled by a piezoelectric actuator. The proposed device has two flexible metallic bellows connected to a rigid reservoir filled with a viscous fluid. When one of the bellows is connected to a vibrating structure a periodic flow passes through a variable internal orifice and the damping effect is produced. The size of the orifice is adjusted by a piezoelectric control system that positions the conical core into a conical cavity. The damper device finite element computational model was developed considering that the valve body is rigid and that the fluid - structure iteration occurs between the fluid and the flexible bellows. This model is discretized using a lagrangean-eulrian formulation. The actuator has a closed flexible metallic structure that amplifies the displacement produced by an internally mounted stack of piezoelectric ceramic layers, and it is also modeled by the finite element method. The damper prototype was built and experimental tests using impulsive and harmonic excitations were conducted to determine its dynamic behavior and also to validate the developed computational models. The simulation and experimental results are compared by curves that relate the damping coefficient with the size of the orifice. Reduced dynamical models are proposed to represent the behavior of the damper device with fixed and variable orifice sizes. A local classic PID controller for the piezoelectric actuator was design to assure that the valve core assume the correct position, providing the commanded damping coefficient. The damper device was applied to a vibration system that represents the model of a quarter-car vehicle. One on-off controller and another fuzzy controller were design to control the vibrations of the vehicle equipped with the proposed active damper. Experimental tests shown that the damping coefficient values, commanded by the global controller, were achieved in time intervals lesser than 10 milliseconds. These results demonstrate the very good performance of the proposed damper device.